Two Cases of Alleged Gang Rape Examined at Forensic Medicine Department of Sher-e-Bangla Medical College (SBMC) Barisal with Opinions Not "Enough to Prove the Allegation" (Anwer Khan Modern Medical College Journal, 2017)
It is one of the most difficult tasks in forensic medicine is to examine alleged victims of sexual offence like rape that happened a few weeks back. There is a chance of miscarriage of justice. Two women were examined in the department of forensic medicine of SBMC. They gave the history of forceful sexual intercourse by several men at midnight while travelling in a bus. After their identification and obtaining informed written consent they were examined by 2 doctors, one is male and the other is female. With heavy responsibility on them the doctors had to proceed with the examination of the victims of alleged gang rape. Clinical examination, laboratory tests of collected specimens and X-ray examination were done. The opinions were that in case of the first victim, her age was around 18 years and in case of 2nd victim, her age was around 17 years and in both victims, no signs of forceful sexual intercourse were present but signs of past sexual intercourse were present. If a consistency between the history given by the victim and signs detected by the examining doctors is established by the investigating legal officer then a positive result is expected from the court of trial but very often this does not happen.Anwer Khan Modern Medical College Journal Vol. 8, No. 2: Jul 2017, P 148-152